Measurements, analyses, and insights on the entire ethereum blockchain network - Lee, Xi Tong (2019)
Blockchain has become increasingly popular with the prevalence of cryptocurrencies and decentralized applications. In this project, interactions in Ethereum’s blockchain will be analysed. Ethereum is a distributed public blockchain network that focuses on creation and execution of codes (smart contracts) for decentralized applications. It is a platform for sharing of information in a global state that is immutable. Ethereum blockchain introduces a novel ecosystem of human users and autonomous agents (smart contracts). In this project, the entire interaction network from entire Ethereum blockchain data is reconstructed in order to analyse the possible interaction types in the network: user-to-user, user-to-contract, contract-to-contract and contract-to-user. Vertices refers to the account in the network (addresses of users or smart contracts) and edges refers to interaction between them. Analyses done on the different interactions in the network reveal new insights by combining information from the four networks. In this project, several graph properties are applied, both local and global properties, to study these networks in detail. From the results, discuss their similarities and differences with social networks and the Web, draw interesting conclusions and highlight important, future research directions. Results and analyses are compiled into a full research paper and submitted, as the first author, to the WebConf (WWW) 2020 conference.